CALL;INSIDE THE GLOBAL SAUDI RELIGIOUS PROJECT - KRITHIKA VARAGUR (COLUMBIA GLOBAL REPORTS, 2020)
"The Call chronicles the House of Saud's vast project to systematically transform the Muslim world in its own image by spreading abroad Wahhabism, its brand of ultraconservative Islam. Using billions of dollars, thousands of personnel, and institutions both governmental and unofficial, "Saudi money" is both more complex and more influential than is commonly believed. Journalist Krithika Varagur traverses three continents to tell the story of the Saudi religious campaign from Indonesia, Nigeria, and Kosovo. She finds Saudi money in all kinds of places, from universities to political parties to extremist and jihadist groups. She meets the people who were swept up in its Cold-War-era peak and those who are still holding up its tarnished international brand today, as well as the victims of the intolerance and fundamentalism that were spread through Saudi dawa, or "call" to Islam. The Call lays out what we really talk about when we talk about Saudi money, and illuminates the global sweep of its ambitions over the last century"--